Empirically derived Coloured Dissolved Organic Matter absorption coefficient using in-situ and Sentinel 3/OLCI in coastal waters of India. Issue 4 (16th February 2022) - Sahay, Arvind; Ali, Syed Moosa; Raman, Mini; Gupta, Anurag; Motwani, Gunjan; Thakker, Rohan; Tirkey, Anima; Solanki, Hitesh A.; Shanmugam, Palanisamy
ABSTRACT: Chromophoric Dissolved Organic Matter (CDOM) is the fraction of dissolved organic matter that absorbs sun light in ultra-violet and visible region of the electromagnetic radiation. CDOM is abundantly found in marine and coastal waters and is very important to studying optical properties of water columns and biogeochemistry of the water. It is a proxy to study dissolved organic carbon pools in marine and freshwater pools. This research aims to establish a relation between CDOM absorption and remote sensing reflectance in coastal waters of India using a large pool of in-situ data set. This study is very significant to studying CDOM distribution, its variability and the coastal processes that influence its distribution on larger time scales (seasonal to decadal changes) through ocean colour sensors. This study presents a new empirical algorithm for estimation of CDOM absorption (412nm) in Indian coastal waters using remote sensing reflectance that has not been reported so far. The study also presents its slope and variability in different regions of coastal waters of India using in-situ data. A large pool of 409 datasets has been generated using NASA bio-Optical Marine Algorithm Dataset/SeaWiFS Bio-Optical Archive and Storage System (NOMAD/SeaBASS) datasets and Indian coastal waters datasets collected during 2014-18 exclusively for coastal waters of India. A power equation is obtained using the ratio of remote sensing reflectance (Rrs412/Rrs555) to derive CDOM absorption with R 2 =0.74. The retrieved absorption coefficient is further validated with independent in-situ data set using another 58 station points with R 2 =0.84. The root mean square error is 0.03 m −1 (with 20% standard error in modelled data). CDOM slope (S412-443 ) is also estimated from in-situ data and it varies from 0.010-0.020 (units nm −1 ) with a mean value of 0.015 (nm −1 ) for Indian coastal waters. CDOM absorption coefficient (412 nm) varies between 0.01-0.8 m −1 for 90% of the stations whereas remaining 10% of the stations show high CDOM absorption coefficient between 1.2- 2.0 m −1 in the study area. This empirically derived algorithm is then applied on Sentinel-3/OLCI derived remote sensing reflectance time series data of whole year 2019 and CDOM absorption coefficient has been retrieved in different regions of coastal waters off Gujarat (India). The seasonal and spatial variability in these regions show that this algorithm is having great potential to retrieve CDOM absorption in coastal areas using high-resolution ocean colour monitors like Sentinel-3/OLCI. This algorithm is highly useful in retrieving CDOM absorption in coastal waters through existing and future ocean colour monitors from space-borne platform.